Pengaruh Tambahan Penghasilan Pegawai Dan Pengembangan Karier Terhadap Kinerja Pegawai Dinas Pendidikan Kota Makassar - Rahman Rahman; Taufik Thahir; Mariati M (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
The purpose of this study was to determine the effect of additional employee income and career development on the performance of Makassar City Education Office employees. The types of data used are quantitative data and qualitative data. Sources of data in this study are primary data and secondary data. The population in this study were 185 employees of the Makassar City Education Office. Determination of the sample using the slovin formula so that the sample in this study was 65 employees at the Makassar City Education Office. The data analysis technique used was descriptive analysis, validity and reliability test, data normality test, multicollinearity test, multiple linear regression analysis test, and hypothesis testing. The results showed that additional employee income and career development had a positive and significant effect on the performance of Makassar City Education Office employees